Evaluation of the performance of equity-sharing schemes administered by the Department of Land Affairs, Worcester district office of the Western Cape Province - Ralehoko, Enoch Ntala (Stellenbosch : Stellenbosch University, 2012)
Thesis (MAgricAdmin)--Stellenbosch University, 2005.